Partnership working and outcomes: do health and social care partnerships deliver for users and carers?. (9th May 2013) - Petch, Alison; Cook, Ailsa; Miller, Emma
Abstract Working in partnership, both across social care and health and with service users, has been a persistent theme of the health and social care modernisation agenda in the United Kingdom. Despite a relatively underdeveloped evidence base, the development of health and social care partnerships has continued to feature in recent policy and legislative initiatives in the United Kingdom. At the same time there has been a major shift in focus towards the outcomes that support services deliver. A central question remaining is whether the policy initiatives driving the development of health and social care partnerships are delivering improved outcomes, particularly the outcomes valued by people who use services. This article outlines research designed to explore this issue across 15 health and social care partnerships in England and Scotland, building from previous research by the Social Policy Research Unit based at the University of York. It sought to assess the extent to which health and social care partnerships deliver the outcomes that people who use services value, and to determine the features of partnership working associated with the delivery of these outcomes. A robust outcomes framework was defined, which provided the basis for interviews with those receiving support from partnerships. Working with three user‐researcher organisations, interviews were completed with 230 individuals in 2006. On the basis of this, some service users were able to identify features of partnership that particularly contributed to improved outcomes. These included continuity of staff and sufficient staff and a range of resources, including the availability of long‐term and preventative services. Given the definitional and methodological complexity surrounding partnership working, and the challenges of attribution, the study faced some limitations in its ability to make wider inferences about partnership and outcomes. A theory of change should be employed in future studies of this type.